Fusion Methods for Biosignal Analysis: Theory and Applications - Salazar, Addisson; Zarzoso, Vicente; Rosa-Zurera, Manuel; Vergara, Luis (Computational Intelligence and Neuroscience, 2017)
Data modalities include electrocardiography (ECG), electroencephalography (EEG), electrocorticography (ECoG), magnetic resonance imaging (MRI), functional MRI (fMRI), positron emission tomography (PET), and diffusion tensor imaging (DTI). Different combinations of DA with other bioinspired methods (bat algorithm, particle swarm optimization, and enhanced fireworks algorithm) and a neural network-based method called extreme learning machine are implemented. [...]Z. Weng et al. design a multimodal fusion method for localization of hub regions in the brain using MRI T1 and DTI.